Arsitektur Sistem Informasi dengan Metode Agile Framework Scrum pada Pelayanan PMKS dan Pemberdayaan Kesejahteraan Sosial - Muhammad Ropianto; Dimas Pradipto; Nanda Jarti; Atman Lucky Fernandes (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to design and implement a database-based information system for managing Social Welfare Issues (PMKS) and Social Welfare Potential and Resources (PSKS) in XYZ Village, XYZ District. Currently, PMKS and PSKS data management is still carried out using Microsoft Excel, which causes data entry errors, such as names, population registration numbers (NIK), and recipient addresses. In addition, data retrieval is difficult, and reports take up a lot of file storage space. Microsoft Excel is also not well integrated and does not allow for direct monitoring. The information system was developed using the Agile approach with the Scrum method and designed using database-based programming, PHP, and MySQL. In the design stage, the Waterfall method was used to design the system, and modeling using Unified Modeling Language (UML) was used to describe the structure and interactions between system components. The results of this research include needs analysis, system design with UML modeling, and 64 tables that support system development. System testing was conducted using Black Box Testing, which involved the PMKS Admin, PSKS Admin, and Public Services related to PMKS and PSKS data management in XYZ Village, XYZ District. The test results showed that the developed information system was successful and could facilitate data management, information retrieval, and report generation, as well as facilitate direct monitoring. In addition, this system requires data classification on the dashboard to display information in a more executive manner, particularly to support annual reports. To maintain the sustainability of this system, it is necessary to improve human resources in the operation and maintenance of the system so that it can continue to function properly and support the management of PMKS and PSKS in XYZ Village, XYZ District.